Factors affecting health care facility utilization in rural areas of Lucknow district - Shukla, Vinita; Gupta, Pratibha (International Journal Of Community Medicine And Public Health, 2018)
Background: Population is increasing rapidly so with the limited resources government alone cannot cater the health of whole population. Private health sector is equally important for the improvement of health of the people. In view of these facts the present study was planned to assess the utilization of health care services (both public and private) and to assess the reasons for visiting that particular health facility (public or private). Methods: Study was cross sectional for 1 year period. Total sample size was 1024. In the present study only rural area was taken. By using multistage stratified random sampling 6 villages were selected and sample came out as 516. Data was analyzed by stata software version -12 for windows and chi square test. Results: 50% respondents visited public, 38% private and 10% visited others (charitable, pharmacies etc.). 62% respondents belonged to lower socio economic status preferred public health care facility. The main reason for visiting public health facility was free services and for private was got cure earlier from that heath facility. Majority of people visited any health facility for illness. (344 out of 516) and 50% of them visited for respiratory diseases. For chronic illness majority (60%) preferred public health care facility. Conclusions: Both public and private health care facilities should be made well equipped and affordable so that people can make choices and not forced to choose particular health facility.